Recent lake expansion triggered the adaptive radiation of freshwater snails in the ancient Lake Biwa. Issue 1 (1st February 2019) - Miura, Osamu; Urabe, Misako; Nishimura, Tomohiro; Nakai, Katsuki; Chiba, Satoshi
Abstract: Lake expansion that leads to the formation of new habitats has potential to drive intralacustrine diversification. The ancient Lake Biwa in central Japan has historically experienced substantial changes in the lake size, and it provides a useful system for evaluating the role of lake-size fluctuations in the diversification of endemic fauna. Here, we used genome-wide DNA analyses and reconstructed the diversification history of the endemic freshwater snails belonging to the subgenus Biwamelania with respect to the geological history of Lake Biwa. We found that two genetically distinct snail lineages independently colonized Lake Biwa and they concurrently and rapidly radiated into 15 extant Biwamelania species. A combination of paleontological evidence and molecular dating technique demonstrated that the radiation of Biwamelania was tightly linked to the latest enlargement of the lake about 0.4 million years ago and suggested that increased ecological opportunity associated with the lake expansion drove the rapid adaptive radiation. We propose that the Biwamelania snails in Lake Biwa offer a promising new system for understanding the association between the geological history of the lake and rapid intralacustrine diversification.